Neutron reaction studies in the rare earth region: First results for the 162Er(n,2n)161Er physics case - Patronis, N.; Aslanoglou, X.; Axiotis, M.; Eleme, Z.; Foteinou, V.; Harissopulos, S.; Kalamara, A.; Kokkoris, M.; Provatas, G.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
In the present work the first experimental results at near two threshold energies for the 162Er(n,2n)161Er reaction study are presented. The reaction cross section was determined at the energies of 11.0 and 11.3 MeV by means of the activation technique. The experimental method and setup is described.